A Seasonal Evaluation of Dynamics of an Aquatic Ecosystem, Kochi, Kerala, India - Radhika.R; Ratheesh kumar C.S.; Salas, P.M; Sujatha, C.H and Chandramohanankumar N (International Journal of Advanced Scientific Research and Management, 2018)
Studies on the hydrological features of the marine and estuarine environment is of great importance since the general distribution, migration and relative abundance of marine and estuarine organisms are greatly influenced by the physico- chemical parameters. Different taxa are affected by wide spectrum of limnological conditions such as pH, nutrient concentrations and salinity. Their number was found to be reduced due to pollution. Variation in pH, salinity temperature regime, solutes, flow, turbidity, dissolved oxygen, substrate composition or pollution level affects fish assemblage. The gain or loss of certain species is a common consequence of the environmental change. The rapid industrialization and the increase in population around the Cochin estuary have resulted in the discharge of a heavy load of the inorganic and organic wastes. Pollution and encroachment are mainly responsible for deterioration of water quality in the water bodies of Kerala.